The number of terms in the expression given is; 2.
<h3>How many term are in the expression given?</h3>
It follows from the task content that the expression given is; (3x^2-3)(3x^2+3).
It therefore follows the converse of law regarding difference of two squares that the expression given can be rewritten as;
= 9x⁴ -9
Read more on difference of two squares;
brainly.com/question/3189867
#SPJ1
Answer:
4592.7
Step-by-step explanation:
Add them up:
4000 + 500 + 90 + 2 + 0.7 = 4592.7
Answer:
x=2
Step-by-step explanation:
Original width = 6
New width 6+x+x
Orignal length 12
New length 12+x+x
A = l*w
160 = ( 6+2x) ( 12+2x)
Factor
160 = 2( 3+x) 2(6+x)
Divide each side by 4
40 = (3+x) (6+x)
FOIL
40 = 18+ 6x+3x+ x^2
40 = 18 +9x+x^2
Subtract 40 from each side
0 = x^2 +9x -22
Factor
0 = (x +11) (x-2)
Using the zero product property
x +11 =0 x-2 =0
x= -11 x=2
Since we cannot have a negative sidewalk
x =2
15 /6÷ 5/6
when we divide fractions we do the reciprocal of the second number that is of
5/6 = 6/5 and then multiply it by the first number
15/6 x 6/5
ans) 3